2011
DOI: 10.1016/j.ajhg.2011.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a 8q21.11 Microdeletion Syndrome Associated with Intellectual Disability and a Recognizable Phenotype

Abstract: We report eight unrelated individuals with intellectual disability and overlapping submicroscopic deletions of 8q21.11 (0.66-13.55 Mb in size). The deletion was familial in one and simplex in seven individuals. The phenotype was remarkably similar and consisted of a round face with full cheeks, a high forehead, ptosis, cornea opacities, an underdeveloped alae, a short philtrum, a cupid's bow of the upper lip, down-turned corners of the mouth, micrognathia, low-set and prominent ears, and mild finger and toe an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 14 publications
8
48
0
Order By: Relevance
“…Zfhx4 expression peaks at the neural precursor stage along with that of the neural stem cell marker Nestin and is inversely correlated with expression of astrocyte marker GFAP (Hemmi et al, 2006) when murine embryonic carcinoma stem-like cells are differentiated with retinoic acid. ZFHX4 also plays a role in human neural development, as ZFHX4 disruption is associated with intellectual disability (Palomares et al, 2011) and congenital bilateral ptosis (McMullan et al, 2002; Nakashima et al, 2008; Palomares et al, 2011). When we examined ZFHX4 expression in previously published gene expression data for the four molecular subtypes of GBM (Verhaak et al, 2010), we found significantly higher expression of ZFHX4 in clinical samples from the Classical subtype as compared to the other subtypes (FDR=0, fold change=1.89; see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Zfhx4 expression peaks at the neural precursor stage along with that of the neural stem cell marker Nestin and is inversely correlated with expression of astrocyte marker GFAP (Hemmi et al, 2006) when murine embryonic carcinoma stem-like cells are differentiated with retinoic acid. ZFHX4 also plays a role in human neural development, as ZFHX4 disruption is associated with intellectual disability (Palomares et al, 2011) and congenital bilateral ptosis (McMullan et al, 2002; Nakashima et al, 2008; Palomares et al, 2011). When we examined ZFHX4 expression in previously published gene expression data for the four molecular subtypes of GBM (Verhaak et al, 2010), we found significantly higher expression of ZFHX4 in clinical samples from the Classical subtype as compared to the other subtypes (FDR=0, fold change=1.89; see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Both deletions and duplications of this region result in some common, non-specific features present in many other microdeletion/ duplication syndromes. Available clinical data presented here, together with cases in the literature [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and databases, demonstrate several consistent phenotypic findings for this interstitial 19p13.3 deletion: macrocephaly, typically combined with prominent forehead and bitemporal narrowing; facial dysmorphic features such as hypertelorism, depressed nasal bridge and nasal root, short philtrum, thin upper lip and ear anomalies; and developmental and speech delay and ID. Similarly, all patients with duplications of the same region consistently showed microcephaly, dysmorphic facial features (wide nasal bridge, depressed nasal root and hypertelorism), feeding problems in infancy, DD and ID, although dysmorphic features and DD/ID were less severe than in the reciprocal deletions.…”
Section: Characterization Of Mechanisms Underlying Interstitial 19p13mentioning
confidence: 99%
“…In fact, using this experimental approach, we and others recently described new microdeletion or microduplication syndromes. [14][15][16][17] Here we report 13 new patients with proximal 19p13.3 submicroscopic rearrangements (11 deletions and 2 duplications) and review patients from the literature (14 cases; 13 deletions and 1 duplication) [18][19][20][21][22] and public genomic databases such as DECIPHER and ISCA Consortium (10 cases; 6 deletions and 4 duplications) for a total of 37 cases. We describe the phenotypic findings and suggest that these patients represent a new microdeletion/duplication syndrome at 19p13.3, with a 113.5 Kb critical region harboring three genes: ZBTB7A, MAP2K2 and PIAS4, the latter being a candidate gene for abnormal head size.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, Palomares et al . () found a 8q21.11 microdeletion in eight cases of intellectual disability with an unusual phenotype and mild finger and toe anomalies (camptodactyly, syndactyly and broadening of the first rays). Lukusa et al .…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally, syndactyly has been related to chromosome abnormalities usually when found in association with malformations of other organs or systems. In humans, Palomares et al (2011) found a 8q21.11 microdeletion in eight cases of intellectual disability with an unusual phenotype and mild finger and toe anomalies (camptodactyly, syndactyly and broadening of the first rays). Lukusa et al (1998) reported a mentally retarded adult male patient with dysmorphic features (facial asymmetry, synophrys, right external strabismus, teeth anomalies and bilateral syndactyly of fingers III-IV and toes II-III evoking zygodactyly) with a partial trisomy 1q deriving from a tandem duplication of the 1q32.3→q42 region.…”
Section: Introductionmentioning
confidence: 99%